Ornamental potential of Caatinga Biome species - Beckmann Cavalcante, Markilla Zunete; Dultra, Daniel Fagner da Silva; Silva, Handerson Leandro da Costa; Cotting, Jarina Coelho; Silva, Sheila Daniella Pereira da; Siqueira Filho, José Alves de (Comunicata Scientiae, 2017)
The reduction or replacement of exotic ornamental plants by native species with ornamental potential is a current trend of landscaping. The insertion in the productive chain of flowers and ornamental plants and availability for commercialization represents a differential in a highly competitive market, attentive to novelties and tending to adopt products of reduced environmental impact besides promoting ex situ conservation. In this sense, the objective was to prospect species of the native flora of the Caatinga Biome that occur in the Valley of the Submédio São Francisco that present aesthetic elements appropriate for use in the landscaping. Incursions were made in the field to identify the species and were described the habit of growth, shape, symmetry, structure, texture and color of structures of higher ornamental value, fragrance, the presence of spines or not with indication of the possibilities of use. A total of 43 species were reported, distributed among herbaceous habit (21), bush habit (11), arboreal trees (9), both one climbing and hardy liana. Among the species indicated, 30.2% belong to the Fabaceae family. The flora of the Caatinga presents species with high ornamental potential for diverse uses and landscape effects. There is a need to stimulate the use of native species of the Caatinga Biome in landscaping projects, whose potential is still little valued.